Neuronal–Glial Interaction in a Triple-Transgenic Mouse Model of Alzheimer’s Disease: Gene Ontology and Lithium Pathways - Rocha, Nicole Kemberly R.; Themoteo, Rafael; Brentani, Helena; Forlenza, Orestes V.; De Paula, Vanessa De Jesus Rodrigues (Frontiers in Neuroscience, 2020)
Neuronal-glial interactions are critical for brain homeostasis, and disruption of this process may lead to excessive glial activation and inadequate pro-inflammatory responses. Abnormalities in neuronal-glial interactions have been reported in the pathophysiology of Alzheimer’s disease (AD), where lithium has been shown to exert neuroprotective effects, including the up-regulation of cytoprotective proteins. In the present study, we characterize by Gene Ontology (GO) the signaling pathways related to neuronal-glial interactions in response to lithium in a triple-transgenic mouse model of AD (3x-TgAD). Mice were treated for eight months with lithium carbonate (Li) supplemented to chow, using two dose ranges to yield subtherapeutic working concentrations (Li1, 1.0g/kg; and Li2, 2.0g/kg of chow), or with standard chow (Li0). The hippocampi were removed and analyzed by proteomics. A neuronal-glial interaction network was created by a systematic literature search, and the selected genes were submitted to STRING, a functional network to analyze protein interactions. Proteomics data and neuronal-glial interactomes were compared by GO using ClueGo (Cytoscape plugin) with p0.05. The proportional effects of neuron-glia interactions were determined on three GO domains: (i) biological process; (ii) cellular component; and (iii) molecular function. The gene ontology of this enriched network of genes was further stratified according to lithium treatments, with statistically significant effects observed in the Li2 group (as compared to controls) for the GO domains biological process and cellular component. In the former, there was an even distribution of the interactions occurring at the following functions: ‘positive regulation of protein localization to membrane’, ‘regulation of protein localization to cell periphery’, ‘oligodendrocyte differentiation’, and ‘regulation of protein localization to plasma membrane’. In cellular component, interactions were also balanced for ‘myelin sheath’ and ‘rough endoplasmic reticulum’. We conclude that neuronal-glial interactions are implicated in the neuroprotective response mediated by lithium in the hippocampus of AD-transgenic mice. The effect of lithium on homeostatic pathways mediated by the interaction between neurons and glial cells are implicated in membrane permeability, protein synthesis and DNA repair, which may be relevant for the survival of nerve cells amidst AD pathology.